Pterional Approach for Anterior Skull Base Midline Meningiomas against “The More The Merrier” Approach: An Institutional Experience - Gowtham, Matham; Gowda, Akhilesh G.B.; Rajeev, Sreenath Prabha; Abraham, Mathew; Easwer, H.V. (Asian Journal of Neurosurgery, 2023)
Objective Anterior midline skull base meningiomas involving olfactory groove, planum sphenoidale, and tuberculum sellae were usually managed with bifrontal craniotomy until the dawn of advanced microsurgical techniques. With the emergence of microsurgical techniques, midline meningiomas could be tackled solely from a unilateral pterional approach. We present our experience with pterional approach in managing anterior skull base midline meningiomas, including the technical nuances and outcomes.Methods Fifty-nine patients who underwent excision of anterior skull base midline meningiomas through a unilateral pterional craniotomy between 2015 and 2021 were retrospectively analyzed. The surgical technique and patient outcomes in the context of visual, behavioral, olfaction, and quality of life were evaluated during the follow-up.Results A total of 59 consecutive patients were assessed over an average follow-up period of 26.6 months. Twenty-one (35.5%) patients had planum sphenoidale meningioma. Olfactory groove and tuberculum sellae meningioma groups consist of 19 (32%) patients each. Visual disturbance was the predominant symptom with almost 68% of patients presented with it. A total of 55 (93%) patients had complete excision of the tumor with 40 patients (68%) achieving Simpson grade II excision, and 11 (19%) patients had Simpson grade I excision. Among operated cases, 24 patients (40%) had postoperative edema among which 3 (5%) patients had irritability and 1 patient had diffuse edema requiring postoperative ventilation. Only 15 (24.6%) patients had contusion of the frontal lobe and were managed conservatively. Five patients (50%) with seizures had an association with contusion. Sixty-seven percent of patients had improvements in vision and 15% of patients had a stable vision. Only eight (13%) patients had postoperative focal deficits. Ten percent of patients had new-onset anosmia. The average Karnofsky score was improved. Only two patients had recurrence during follow-up.Conclusion A unilateral pterional craniotomy is a versatile approach for the excision of anterior midline skull base meningioma, even for the larger lesions. The ability of this approach in the visualization of posterior neurovascular structures at the earlier stages of surgery while avoiding the opposite frontal lobe retraction and frontal sinus opening makes this approach more preferable over the other approaches.
Keywords: anterior midline skull base meningioma; olfactory groove; planum sphenoidale; pterional approach; tuberculum sella